1997
DOI: 10.1161/01.cir.96.4.1152
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Insulin-Potassium Therapy for Treatment of Acute Myocardial Infarction

Abstract: The findings indicate that GIK therapy may have an important role in reducing the in-hospital mortality after acute myocardial infarction. The value of this therapy in the era of thrombolysis and acute revascularization by primary angioplasty can be fully resolved only by conducting a large randomized mortality study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
220
2
14

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(238 citation statements)
references
References 40 publications
2
220
2
14
Order By: Relevance
“…Insulin, as part of the glucose-insulin-potassium (GIK) combination, has long been used as a therapy for acute myocardial infarction and has been shown to significantly decrease in-hospital mortality (8) and overall mortality (24). In isolated cardiac myocytes subjected to ischemia and reoxygenation, administration of insulin reduces apoptosis and protects cells against irreversible injury (12).…”
mentioning
confidence: 99%
“…Insulin, as part of the glucose-insulin-potassium (GIK) combination, has long been used as a therapy for acute myocardial infarction and has been shown to significantly decrease in-hospital mortality (8) and overall mortality (24). In isolated cardiac myocytes subjected to ischemia and reoxygenation, administration of insulin reduces apoptosis and protects cells against irreversible injury (12).…”
mentioning
confidence: 99%
“…In consequence, there is an increase of glucose uptake into cardiac muscle. It remains unclear whether the effect of GIK relies on a decrease of FFA and/or an increase in glucose utilization [36]. As insulin decreases blood glucose and potassium levels, potassium and glucose are integral constituents of the GIK regimen to maintain normoglycaemia and normokalaemia.…”
Section: Discussionmentioning
confidence: 99%
“…GIK has been studied in acute myocardial infarction [11,36,37] and cardiac surgery [38][39][40], albeit with variable results and thus no overall benefit [41]. Possible reasons include use of different doses of insulin, failure to maintain normoglycaemia, and introduction after thrombolysis where high blood sugar levels may have enhanced the degree of reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…72, 73 Despite that long history, results from trials employing GIK in MI and cardiac surgery are often inconclusive due to small sample sizes and differences of study design and GIK infusions. 74 The dose shown to suppress free fatty acid uptake in the myocardium is 30 g of glucose, 50 units of insulin, and 80 mmol of potassium chloride per liter at 1.5 mL/kg/h. 68 A meta-analysis of randomized clinical trials involving GIK infusions in MI indicated a significant reduction in inpatient mortality for patients receiving GIK compared with conventional treatment.…”
Section: Cardiovascularmentioning
confidence: 99%
“…4 Major criticisms in the majority of trials include defective study design and concomitant therapies with predated thrombolytic and β-blocker therapies. 74 Contemporary studies continue to show conflicting results with GIK infusions. In 1998, a study including 407 MI patients randomized to GIK or control showed a 66% reduction of in-hospital mortality when GIK was added to reperfusion therapy.…”
Section: Cardiovascularmentioning
confidence: 99%